2017
DOI: 10.1038/bjc.2017.225
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear expression of Gli-1 is predictive of pathologic complete response to chemoradiation in trimodality treated oesophageal cancer patients

Abstract: Background:Predictive biomarkers or signature(s) for oesophageal cancer (OC) patients undergoing preoperative therapy could help administration of effective therapy, avoidance of ineffective ones, and establishment new strategies. Since the hedgehog pathway is often upregulated in OC, we examined its transcriptional factor, Gli-1, which confers therapy resistance, we wanted to assess Gli-1 as a predictive biomarker for chemoradiation response and validate it.Methods:Untreated OC tissues from patients who under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 46 publications
0
22
0
Order By: Relevance
“…We have demonstrated a correlation between SMO and its downstream target GLI‐1 expression, but not with p53 expression. Previous studies clearly indicated that the HhP is up‐regulated in many types of cancer, including medulloblastoma, pancreatic cancer, prostate cancer and oesophageal cancer . It has been further proposed that the HhP plays a crucial role in cancer development and progression .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have demonstrated a correlation between SMO and its downstream target GLI‐1 expression, but not with p53 expression. Previous studies clearly indicated that the HhP is up‐regulated in many types of cancer, including medulloblastoma, pancreatic cancer, prostate cancer and oesophageal cancer . It has been further proposed that the HhP plays a crucial role in cancer development and progression .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies clearly indicated that the HhP is up-regulated in many types of cancer, including medulloblastoma, pancreatic cancer, prostate cancer and oesophageal cancer. [10][11][12][13] It has been further proposed that the HhP plays a crucial role in cancer development and progression. 14 In contrast to the findings of Lee et al, 15 we did not find a correlation between GLI-1 expression and lymph node stage.…”
Section: Discussionmentioning
confidence: 99%
“…A monoclonal anti-Shh antibody, 5E1 or LED225 (Novartis) was able to increase the efficacy of radiation treatment in patient-derived xenograft models of cervical and esophageal cancer [ 145 , 146 ]. Clinically, expression of Shh pathway (Gli1 staining) was associated with the efficacy of esophageal patients treated with chemoradiation and surgery, in two cohorts of patients ( n = 60 and n = 167) [ 147 ]. Moreover, activation of Shh pathway is associated with tumor relapse after radiotherapy in patients with head and neck carcinoma and cervical carcinoma [ 148 , 149 ].…”
Section: Shh Pathway and Resistance To Radiotherapymentioning
confidence: 99%
“…Of the three factors, GLI1 has emerged as a critical oncogene, having transcriptional activity as the distal effector of both the canonical Hh pathway as well as the non-canonical oncogenic KRAS/BRAF pathway (19). Additionally, oncogenic GLI1 activity is often linked to chemo-resistance (20)(21)(22)(23)(24)(25) due in part to GLI1's transcriptional regulation of several oncogenes involved in critical processes at all stages of cellular life ranging from proliferation and survival to cycle checkpoints (26). We have previously reported that GLI inhibition led to significant DNA damage, and subsequent apoptosis in colon carcinoma cells due to an extended pause in DNA replication licensing via down-regulation of CDT1, a critical DNA replication licensing factor and transcriptional target of GLI1 (27).…”
Section: Introductionmentioning
confidence: 99%